Fostering Better Chemistry Learning Outcomes with the Cooperative Integrated Reading and Composition Learning Model - Mustofa, Nur; Wahyuni, Indah Sri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study was to improve the chemistry learning outcomes by implementing the cooperative learning model of the Cooperative Integrated Reading and Composition type. Methodology: The subjects in this study were 18 students of class X of LKMD Sukaramai Tapung Hulu Senior High School. While the object of this study is the application of the cooperative learning model of the Cooperative Integrated Reading and Composition type to improve the chemistry learning outcomes of class X students of LKMD Sukaramai Tapung Hulu Senior High School. Main Findings: Based on the research results, the implementation of cooperative learning strategies of the Cooperative Integrated Reading and Composition type in the learning process in class X of LKMD Sukaramai Tapung Hulu Senior High School increased student learning outcomes. From the analysis of data on the success of the action, it was found that there was an increase in the number of students who had scores above 65 after the action compared to the number of students who had scores above 65 before the action with a percentage of completion of 33.3%, and in the first daily test increased by 55.6%. While in the second daily test, all students (100%) obtained a minimum score or above 65. Novelty/Originality of this study: The novelty of this study is to determine the effectiveness of implementing the cooperative integrated reading and composition type of cooperative learning model to improve chemistry learning outcomes.